2019
DOI: 10.1111/chd.12750
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of risk prediction scores in pregnant women with congenital heart disease

Abstract: Objective: To assess performance of risk stratification schemes in predicting adverse cardiac outcomes in pregnant women with congenital heart disease (CHD) and to compare these schemes to clinical factors alone.Design: Single-center retrospective study.Setting: Tertiary care academic hospital. Patients: Women ≥18 years with International Classification of Diseases, NinthRevision, Clinical Modification codes indicating CHD who delivered between 1998 and 2014. CARPREG I and ZAHARA risk scores and modified World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 21 publications
2
6
1
4
Order By: Relevance
“…Based on the ratio of observed to estimated number of events, the ZAHARA risk model provided the most accurate risk estimate of maternal complications in our study population. Our findings differ from conclusions of other similar studies [11][12][13][14]21], but these studies did not only include CHD patients. The ESC guidelines 2018 on pregnancy indicated that the mWHO classification is considered the best model for the estimation of maternal cardiac risk [5].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Based on the ratio of observed to estimated number of events, the ZAHARA risk model provided the most accurate risk estimate of maternal complications in our study population. Our findings differ from conclusions of other similar studies [11][12][13][14]21], but these studies did not only include CHD patients. The ESC guidelines 2018 on pregnancy indicated that the mWHO classification is considered the best model for the estimation of maternal cardiac risk [5].…”
Section: Discussioncontrasting
confidence: 99%
“…Maternal adverse cardiac events occurred in 8% of our study population, which is similar to the incidence of the cardiac events reported in other studies [7][8][9][11][12][13][14][15][16][17][18][19][20]. There is a certain variation of event rates among different studies, ranging from 6.7 to 25%, which is likely due to the heterogeneity of the study populations.…”
Section: Discussionsupporting
confidence: 86%
“…Of the 77 women with cardiac disease in that study, 9% had cardiac complications during the first pregnancy and 6% had cardiac complications during the second pregnancy; the difference was not statistically significant. We found that the CARPREG I and mWHO risk scores were associated with higher OR of cardiac complications with higher scoring as described previously [14]. There was no clear signal indicating that parity per se was associated with a higher risk of having a cardiac complication during subsequent pregnancies, which is valuable information in prepregnancy counselling (Table 3).…”
Section: Discussionsupporting
confidence: 80%
“…El riesgo de complicaciones durante el embarazo depende de factores como el tipo de enfermedad cardiaca, la función ventricular y valvular, la clase funcional, la presencia de cianosis, la presión de la arteria pulmonar, las comorbilidades. Por otra parte, se han publicado múltiples esquemas para la estratificación del riesgo con exactitud variable en el nivel de predicción 4 . Estos predictores y las puntuaciones de riesgo son herramientas que deben ser usadas teniendo en cuenta la información específica de la enfermedad cardiaca y la condición clínica de cada paciente 5 .…”
Section: Introductionunclassified